Compactação do solo e intervalo hídrico ótimo no crescimento da parte aérea e produtividade da cultura do milho - Freddi, Onã da Silva [UNESP]; Centurion, José Frederico [UNESP]; Aratani, Ricardo Garcia [UNESP]; Beutler, Amauri Nelson [UNESP] (My University, 2008)
The aim of this work was to evaluate the effect of soil compaction caused by tractor wheel traffic on the limiting water range (LLWR), shoot growth and levels of compaction and four replications in a completely randomized experimental design. Soil samples with preserved structure were collected in the layers: 0.02-0.05; 0.08-0.11; 0.15-0.18 and 0.22-0.25m to determine macroporosity, microporosity, total porosity, bulk density, resistance to penetration and LLWR. The evaluated corn parameters were: plant and first spike height, steam diameter, number of spikes per plant, plant dry matter, dry matter of 1000 seeds and seed productivity. The soil compaction restricted all corn parameters except the number of spikes per plant and dry matter of 1000 seeds. The LLWR was reduced by the soil resistance to penetration, even in the tilled soil with bulk density of 1.12 Mg m-3. Only the treatment with 11 Mg tractor, repeated four times on the area, demonstrated bulk density above critical bulk density in the LLWR that was 1.37 Mg m-3, where the seed productivity was significantly smaller.
Soil compaction and least limiting water range on corn shoot growth and seed productivity
Keywords: Bulk density; Soil resistance to penetration; Zea mays; Agriculture; Compaction; Density (specific gravity); Plants (botany); Porosity; Seed; Soils; bulk density; compaction; penetration; soil structure